Simultaneous Spray Self‐Assembly of Highly Loaded ZIF‐8–PDMS Nanohybrid Membranes Exhibiting Exceptionally High Biobutanol‐Permselective Pervaporation1. Issue 22 (7th April 2014) - Fan, Hongwei; Shi, Qi; Yan, Hao; Ji, Shulan; Dong, Jinxiang; Zhang, Guojun
Abstract The ability to obtain a maximum loading of inorganic nanoparticles while maintaining uniform dispersion in the polymer is the key to the fabrication of mixed‐matrix membranes with high pervaporation performance in bioalcohol recovery from aqueous solution. Herein, we report the simultaneous spray self‐assembly of a zeolitic imidazolate framework (ZIF)–polymer suspension and a cross‐linker/catalyst solution as a method for the fabrication of a well‐dispersed ZIF‐8–PDMS nanohybrid membrane with an extremely high loading. The ZIF‐8–PDMS membrane showed excellent biobutanol‐permselective pervaporation performance. When the ZIF‐8 loading was increased to 40 wt %, the total flux and separation factor could reach 4846.2 g m−2 h−1 and 81.6, respectively, in the recovery of n‐butanol from 1.0 wt % aqueous solution (80 °C). This new method is expected to have serious implications for the preparation of defect‐free mixed‐matrix membranes for many applications.